German religious women in late Ottoman Beirut : competing missions - Hauser, Julia. (Studies in Christian Mission, 2015)
In German Religious Women in Late Ottoman Beirut. Competing Missions , Julia Hauser offers a critical analysis of the German Protestant Kaiserswerth deaconesses' orphanage and boarding school for girls in late Ottoman Beirut as situated within the larger field of educational development in the city. Drawing, among other sources, on the deaconesses' largely unpublished letters home, her study illuminates that the only way missionary organizations like the deaconesses' could succeed was by entering into negotiations with their local environment, adapting their agenda in the process. Mission, therefore, was shaped not merely at home, but by conflictual negotiations on the periphery ‒ a perspective quite different from the top-down isolationist perspective of earlier research on missions.